Expression of Personal Spiritual Concepts in Uzbek Proverbs - Tojiyeva Gulbahor Nomozovna (Zien Journals, 2023)
This article describes the expression of the concepts of personal spirituality in Uzbek folk proverbs. the specific meanings of concepts denoting the spirituality of a person in folk proverbs are proved based on examples taken from artistic works. It has been scientifically proven that proverbs show the rich cultural-educational, socio-economic, and spiritual image of the people.
Keywords: Folklore; proverb; linguacultural; sociopragmatic